Strengthening Multimodal Literacy and Self-Talk in Learning Research Methodology: A Factorial Design Study on the English Language Education Students - Yusti Arini; Ika Sulistyarini; Ambar Winarti; Maria Wulandari; Sabariyanto (Attractive : Innovative Education Journal, 2026)
This research aims to analyze the effect of strengthening multimodal literacy and self-talk in learning research methodology as well as the interaction effect of these two variables. This research is a pre-test and post-test control group experimental design with a 2 x 2 factorial design. The research subjects were selected using the Cluster Random Sampling technique; one experimental group with 31 students given a multimodal learning approach and one control group with 33 students given a monomodal learning approach. Data in this study were collected using achievement tests and self-talk questionnaire. The experimental group received nine sessions of treatment involving multimodal literacy and self-talk reinforcement. For the control group, treatment was also given 9 times using monomodal media and without self-talk reinforcement. The data were analyzed using descriptive statistics, Shapiro-Wilk test and Levene test for pre-requisite test, and Two-Way ANOVA for hypothesis testing. The results show that there is no significant influence of the learning approach or self-talk reinforcement on research methodology competence; however, there was an interaction effect between the two variables. Thus, it is important to conduct research methodology learning that combines a multimodal learning approach using various techniques and media with self-talk reinforcement.